2009
DOI: 10.17221/594-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting packed and unpacked fluid milk consumption

Abstract: This article identifies consumer characteristics associated with preferences toward fluid milk alternatives. Using consumer survey data from Samsun province of Turkey and Multinomial Logit model, unpacked and packed fluid milk preferences were analyzed. Based on the results, 14.1% of respondents consumed only unpacked fluid milk, 58.2% consumed only packed fluid milk and 27.7% of respondents consumed both unpacked and packed fluid milk at least once a weak. Multinomial Logit model results indicated that better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
3
4
0
Order By: Relevance
“…In consideration, to marginal effects the consumers who believe that packed milk is hygienic and healthy are by 55.15% more likely to Economics Research International 7 prefer packed milk instead of unpacked milk. Similar studies support our study findings by Pazarlioǧlu et al [5], Akbay and Tiryaki [9], Kilic et al [13], Günden et al [8].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…In consideration, to marginal effects the consumers who believe that packed milk is hygienic and healthy are by 55.15% more likely to Economics Research International 7 prefer packed milk instead of unpacked milk. Similar studies support our study findings by Pazarlioǧlu et al [5], Akbay and Tiryaki [9], Kilic et al [13], Günden et al [8].…”
Section: Resultssupporting
confidence: 93%
“…Günden et al [8] emphasized that households with more members could be closely correlated with budget constraints, which imply that this group's demand for unpacked milk is incomeand/or price-oriented. Similar to our study results, Kilic et al [13] found that increasing household size decreased the probability of consuming packed fluid milk compared to unpacked fluid milk. Tiryaki and Akbay [16] implied that the household size was getting bigger; the household would tend to consume unprocessed fluid milk instead of consuming processed fluid milk.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In Turkey, there have been many studies conducted about consumer behavior, preferences, and factors effecting the consumption of milk or dairy products (Hasipek & Kaleli 2002;Hatirli et al 2004;Celik et al 2005;Akbay & Tiryaki 2008;Kilic et al 2009;Ates & Ceylan 2010;Tiryaki & Akbay 2010;Seker et al 2012;Karakaya & Akbay 2013). The food safety subject has also been studied in the farm, collection center and dairy industry sectors.…”
Section: Introductionmentioning
confidence: 99%